Did the COVID-19 Pandemic Prolong the Time Till Diagnosis and Worsen Outcomes for Children with Acute Appendicitis? - Idilė Vansevičienė; Danielė Bučinskaitė; Dalius Malcius; Aušra Lukošiūtė-Urbonienė; Mindaugas Beržanskis; Emilis Čekanauskas; Vidmantas Barauskas (Medicina, 2021)
Background and Objectives: Our aim was to see if the COVID-19 pandemic led to an increase of time until diagnosis, operation, and time spent in Emergency room (ER), and if it resulted in more cases of complicated appendicitis and complication rates in children. Materials and Methods: We conducted a retrospective analysis of patients admitted to the Pediatric Surgery Department with acute appendicitis during a 4-month period of the first COVID-19 pandemic and compared it to the previous year data—the same 4-month period in 2019. Results: During the pandemic, the time spent in the ER until arriving at the department increased significantly 2.85 vs. 0.98 h p < 0.001, and the time spent in the department until the operation 5.31 vs. 2.66 h, p = 0.03. However, the time from the beginning of symptoms till ER, operation time and the length of stay at the hospital, as well as the overall time until operation did not differ and did not result in an increase of complicated appendicitis cases or postoperative complications. Conclusions: The COVID-19-implemented quarantine led to an increase of the time from the emergency room to the operating room by 4 h. This delay did not result in a higher rate of complicated appendicitis and complication rates, allowing for surgery to be postponed to daytime hours if needed.